La création franco-chinoise dans sa matérialité. Le symbolisme dans l’œuvre plastique de Xuefeng Chen et son rapport à la matière - Guillaume Thouroude (Modern Languages Open)
This article analyses the work of the female artist Xuefeng Chen from the perspective of materiality and the symbolic power of the materials used. In doing so, it juxtaposes Xuefeng’s art with the philosophical thought of Gaston Bachelard, particularly his essays on the impact of fire, water and air on the human psyche. The article focuses on the symbolic dimension inherent in each material manipulated by the artist. Born in Yunnan and residing in Lyon, Xuefeng Chen draws from personal experience to create universal objects that bring together the traditions of southeastern China and French autofictional writing: a floating temple made of white muslin (vernacular architecture) is adorned with embroideries (a popular art form in Yunnan) that narrate accidents, injuries and abortions (the narrative voice of a contemporary woman). In works that sometimes draw from Western trends such as those of Louise Bourgeois or Nikki de Saint Phalle, it becomes apparent that Xuefeng’s work engages in a dialogue between traditions to dialectically work with materials: each medium addressed is stretched between two contradictory symbolic forces that the artist refuses to resolve. While her embroideries stage the conflict between the pleasure of lightness and the suffering of rupture, the ceramic sculptures oscillate between a desire for proliferation and the acknowledgement of a fundamental human fragility. RÉSUMÉ Cet article analyse l’œuvre de Xuefeng Chen en s’appuyant notamment sur la pensée du philosophe Gaston Bachelard. L’article s’attache à la dimension symbolique propre à chaque matière travaillée par l’artiste. Née dans le Yunnan et vivant à Lyon, Xuefeng Chen puise dans son expérience personnelle et intime pour créer des objets universels qui font se rencontrer les traditions du sud-est chinois et l’écriture autofictionnelle française: un temple flottant de mousseline blanche (architecture vernaculaire) est recouvert de broderies (art populaire du Yunnan) qui racontent des accidents, des blessures et des avortements (voix narrative d’une femme d’aujourd’hui). Dans des œuvres qui empruntent parfois à des tendances occidentales de Louise Bourgeois ou de Nikki de Saint Phalle, il apparaît que l’œuvre de Xuefeng Chen opère un dialogue entre les traditions pour travailler les matières de manière dialectique: chaque medium abordé est tendu entre deux forces symboliques contradictoires que l’artiste refuse de résoudre. Tandis que ses broderies mettent en scène le conflit entre le plaisir de la légèreté et la souffrance de la déchirure, les sculptures en céramique font osciller le sens entre un désir de prolifération et la constatation d’une fragilité humaine fondamentale. English title: Franco-Chinese Creation in Its Materiality: The Symbolism in the Visual Art of Xuefeng Chen and Its Relationship to the Material